Retrospective of five years research of school leadership in Asia (2018–2022): A scientometric paradigm - Nurhuda Nurhuda; Novri Gazali; Khairul Hafezad Abdullah; Norazlinda Saad; Edi Setiawan; Joseph Lobo (International Journal of Evaluation and Research in Education (IJERE), 2023)
This research scrutinized the scientometric objectivity of school leadership research in Asia. Publication records between 2018 and 2022 were extracted from Scopus and the Web of Science, after which the bibliographic data set was administered using ScientoPy and VOSviewer. A total of 958 publications were issued over the last five years, with 2020 having the highest number of published articles. The International Journal of Innovation, Creativity and Change was the most productive source (26 papers), Hallinger was the most published author, and “Examining school leadership effects on student achievement: the role of contextual challenges and constraints” had the most significant impact with 33 citations. The top 10 keywords were “leadership,” “higher education,” “transformational leadership,” “principal,” “education,” “school principals,” “school leadership,” “instructional leadership,” “educational leadership,” and “organizational commitment.” With 240 publications, Indonesia was Asia’s leading contributor in this research domain. The results indicated that school leadership research is important. It is recommended that future researchers extend this research to other regions, such as Africa, North America, South America, Antarctica, Europe, and Australia, to gain a fuller picture of school leadership studies across the world.